Health Management and Disease Control of Broiler Chicken in Din Dahlan Farming Seri Kembang III village Payaraman Subdistrict Ogan Ilir Regency - Fitra Yosi; Mutia Nurrahmandani (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Broiler chickens are easily to be inffected by disease and bring some disadvantages because of the effect from attacking diseases the health of broiler farms is affected the environment. The existence of health management and control of broiler chicken disease in Din Dahlan Ranch, Seri Kembang III Village, Payaraman District, Ogan Ilir Regency. The purposes of this study are to observe and study the management of disease control, especially in the field of broiler farms. This research was carried out for 2 months by collecting data directly to the research location of the owner of Din Dahlan ranch and distributing questionnaires. The result is showed that Din Dahlan Farms implemented a vaccination program, provision of medicines, aspects of biosecurity and sanitation in broiler chickens. So that this research shows that the Health Management and Control of Broiler Chickens in Din Dahlan Farms is already good.